2021
DOI: 10.3390/inorganics9120089
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Combustion Synthesis, Crystal Structure and Luminescence of Cr3+ and Mn4+ Ions in Nanocrystalline SrAl4O7

Abstract: A series of strontium dialuminate SrAl4O7 nanopowders with the grossite-type structure doped with chromium and manganese ions were synthesized by the combined sol–gel solution combustion method with use of two different strontium salts. The Cr3+ and Mn4+ ions concentrations were varied from 0.05 to 5 at.%. Evolution of phase composition, crystal structure, and microstructural parameters of the nanocrystalline materials depending on the synthesis conditions, temperature of thermal treatment, and dopant content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…[15,16]). The inset in Figure 6b shows the R lines of this center in comparison with a similar center previously observed by us in SrAl4O7:Cr 3+ [13]. The second one also has two narrow lines at 683.3 and 686.7 nm, which are superimposed on a broad emission band stretching up to 800 nm.…”
Section: Luminescent Propertiessupporting
confidence: 82%
See 4 more Smart Citations
“…[15,16]). The inset in Figure 6b shows the R lines of this center in comparison with a similar center previously observed by us in SrAl4O7:Cr 3+ [13]. The second one also has two narrow lines at 683.3 and 686.7 nm, which are superimposed on a broad emission band stretching up to 800 nm.…”
Section: Luminescent Propertiessupporting
confidence: 82%
“…This center marked as Cr2 in SrAl4O7:Cr 3+ manifests a broad emission band centered at about 780 nm, with excitation bands at about 470 and 630 nm. It should be mentioned that the Cr 3+ center in a weak crystal field exhibiting a broadband emission was not discussed in our recent study of SrAl 4 O 7 :Cr 3+ [13]. Having observed this new center in the studied calcium aluminate, we revisited the earlier results and carried out additional measurements for SrAl 4 O 7 :Cr 3+ samples calcined at 1400 • C. The examinations confirmed that the Cr center in a weak crystal field does exist in this host (see Figure 7).…”
Section: Luminescent Propertiesmentioning
confidence: 83%
See 3 more Smart Citations